Ambulatory assessment characteristics predict the clinical course of Premenstrual Dysphoric Disorder - Beddig, Theresa; Kühner, Christine (Psychotherapy and psychosomatics, 2020)
Premenstrual dysphoric disorder (PMDD, DSM-5) is characterized by severe key mood symptoms (mood lability, irritability, depression, anxiety) accompanied by cognitive and/or physical symptoms starting during the week before menses (late luteal phase) and becoming minimal or absent within the first week after menses onset. Symptoms must be severe enough to cause significant suffering or psychosocial impairment. The symptom pattern must have been present during a majority of cycles within the past year and may not merely represent a premenstrual exacerbation of another mental disorder. Research has provided satisfactory empirical evidence for the diagnosis which finally led to its inclusion in DSM-5 and ICD-11 [1].
Gesehen am 21.07.2025